E-Journal Publishing In Malaysia: From Single Journal System To Publishing Through A Host - Zainab, Awang Ngah; Ang, T.F.; Abrizah, Abdullah (SAGE Publications, 2005)
Presents a brief overview of the various Malaysian scholarly electronic journals available on the Internet. Currently, there are thirteen Malaysian e-journals found on the Web. Provision for access to articles varies from one or two volumes only to full-text access to PDF files of all issues from browsing or search modules. Focuses on EJUM (Electronic Journal of the University of Malaya), an e-journal host. This host is developed using Microsoft Visual Studio.NET, where the language used is C#. There are 3 journals currently parked in this host, Malaysian Journal of Computer Science (MJCS), Malaysian Journal of Library and Information Science (MJLIS), and Journal of Problem-Based Learning (JPBL). As a host EJUM is modeled for uniformity, especially in terms of searching, retrieval and display of search results. Independence is ensured for each journal editorials in terms of editorial policy, style of publication and content. EJUM provide an avenue for scholarly journals to be hosted by a single system, making it easy for academic publishers to be involved in electronic publishing and to electronically manage article contributions. It provides journal publishers with the means to archive their older issues, automates the editorial and refereeing process, provide an efficient and varied search and retrieval options, provide users with a personalization service that profiles their search interests and alert them of any new articles subsequently published; and provide publishers with subscriber’s and access reports. At present, this host allows refereed journal publishers to “park” within the system gratis.